Evaluasi Implementasi Pembelajaran Al-Qur'an Metode Ummi Dalam Meningkatkan Kompentensi Membaca Al-Qur'an Siswa Sdit Nurhikmah Bekasi - Aulia, Siti Nur Haliza; Sudin, Mahmudin (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2025)
Evaluation is one of the components of the Islamic education system that must be carried out systematically and planned as a tool to measure the success or targets to be achieved in the educational process or learning process. Currently, Islamic-based schools that focus on the quality of their graduates in front of parents emphasize the ability to read the Al-Qur'an properly and correctly in accordance with the rules of tajwid. However, the current phenomenon is the lack of improvement in learning the Al-Qur'an, especially in reading the Al-Qur'an in some schools. The Ummi method helps institutions and teachers improve the ability to manage Al-Qur'an learning that is effective, easy, fun, and touching. This research uses a qualitative approach with a case study design. Data collection was carried out using interview, participatory observation, and documentation techniques. The research informants are the Deputy Head of Curriculum, students, and the Ummi Coordinator.